2020
DOI: 10.1021/acsomega.9b04064
|View full text |Cite|
|
Sign up to set email alerts
|

Pyramid-Shaped PEG-PCL-PEG Polymeric-Based Model Systems for Site-Specific Drug Delivery of Vancomycin with Enhance Antibacterial Efficacy

Abstract: Antibacterial resistance remains a major global problem due to frequent prescriptions, leading to significant toxicities. To overcome the limitations of antibiotic therapy, it is highly desirable to provide site-specific delivery of drugs with controlled release. Inspired by the biocompatible, biodegradable, and site-specific mimicking behavior of poly(ethylene glycol) (PEG) and poly(caprolactone) (PCL), we developed vancomycin-PEG-PCL-PEG conjugates to maximize the pharmacological effects and minimize the sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…The use of blood hemolysis tests determined the biocompatibility of the nanocarriers. A minor modification to the previously published procedure technique was performed [29].…”
Section: In Vitro Hemolysis Assaymentioning
confidence: 99%
“…The use of blood hemolysis tests determined the biocompatibility of the nanocarriers. A minor modification to the previously published procedure technique was performed [29].…”
Section: In Vitro Hemolysis Assaymentioning
confidence: 99%
“…PCL is a semicrystalline, hydrophobic material that is compatible with a wide range of other polymer materials. Due to its polyvalent nature, fabrication ease, and good biocompatibility, it is established as a polymer of choice with a wide range of applications in targeted novel drug delivery and tissue engineering [ 31 ]. Hydrogels have been used extensively in the development of smart delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…PEG is a biodegradable polymer only when copolymerized with other biodegradable polymers, such as polyglycolic acid (PGA) and poly-L-lactide acid (PLA) [ 27 ]. Many scientists have reported that PEG-based surfaces offer protection from external contamination; however, the protection level is not very high and a certain number of bacteria can get onto the polymer [ 28 , 29 , 30 , 31 ]. This is why the main goal is to find an antibacterial agent that can efficiently eliminate bacterial contamination, while at the same time being biocompatible with the human body [ 32 ].…”
Section: Introductionmentioning
confidence: 99%